ANSWER
![\begin{gathered} x=-4 \\ x=2+2\sqrt[]{3i} \\ x=2-2\sqrt[]{3i} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vx3nke05q2vx7wgfsnbf9b0wolygmriaok.png)
Step-by-step explanation
We want to solve the polynomial:
![x^3+64=0](https://img.qammunity.org/2023/formulas/mathematics/college/wsqyjvq969rh1x4cnm411lgfl1qdyvqop0.png)
First, subtract 64 from both sides of the equation:
![\begin{gathered} x^3+64-64=0-64 \\ x^3=-64 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/taqcb9mxa4xoykdac3wx7ju4at6r9d04a9.png)
For a cubic polynomial in the form x³ = f(a), the solutions are:
![x=\sqrt[3]{f\left(a\right)},\: \sqrt[3]{f\left(a\right)}(-1-√(3)i)/(2),\: \sqrt[3]{f\left(a\right)}(-1+√(3)i)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/naqbxd5ga2k6yn7g89unr28qhlvp65mem4.png)
From the given polynomial, f(a) = -64
Therefore, the solutions of the polynomial are:
![\begin{gathered} x=\sqrt[3]{-64};,\: \sqrt[3]{-64}\frac{-1-\sqrt[]{3}i}{2};\text{ }\sqrt[3]{-64}\frac{-1+\sqrt[]{3}i}{2} \\ \Rightarrow x=-4;-4\cdot\frac{-1-\sqrt[]{3}i}{2};-4\cdot\frac{-1+\sqrt[]{3}i}{2} \\ \Rightarrow x=-4;-2\cdot-1-\sqrt[]{3}i;-2\cdot-1+\sqrt[]{3}i \\ \Rightarrow x=-4;x=2+2\sqrt[]{3i};x=2-2\sqrt[]{3i} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/474dbi9fiuknyvrfazpg4wb4nmszj3eplz.png)
Those are the solutions.